2017
DOI: 10.1007/s10668-017-9941-9
|View full text |Cite
|
Sign up to set email alerts
|

Who is the bigger culprit? Studying impacts of traffic and land use on noise levels in CBD area of Karachi, Pakistan

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported License Newcastle University ePrints-eprint.ncl.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In recent years, excessive noise has also gained a different characteristic besides being a factor that causes discomfort. It is observed that when people are exposed to sound waves at high intensities for long periods of time, they lose their health (Kephalopoulos et al 2014 ; Gupta et.al 2018 ; Kumar et al 2018 ; Mehdi et al 2018 ). Development of the transportation network, proliferation of motor vehicles, widespread mechanization and failures in protecting densely populated residential areas from noise due to unplanned rapid urbanization cause many problems in terms of public health.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, excessive noise has also gained a different characteristic besides being a factor that causes discomfort. It is observed that when people are exposed to sound waves at high intensities for long periods of time, they lose their health (Kephalopoulos et al 2014 ; Gupta et.al 2018 ; Kumar et al 2018 ; Mehdi et al 2018 ). Development of the transportation network, proliferation of motor vehicles, widespread mechanization and failures in protecting densely populated residential areas from noise due to unplanned rapid urbanization cause many problems in terms of public health.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome showed that noise levels, sources and the period the noise level reaches its peak vary with population density. Across Specifically, studies [1,11,15] observed that relationship exists between land use and noise pollution. Non-traffic parameters, such as land use type and pattern as well as physical distance from a given source, plays an important role in assessing noise level [16,5,17].…”
Section: Empirical Studies Overviewmentioning
confidence: 99%